Safety and feasibility of the use of a bevacizumab-methylcellulose mixture as an adjunct to glaucoma surgery: a pilot study - Paula,Jayter Silva (2015)
ABSTRACT Bevacizumab, a monoclonal anti-vascular endothelial growth factor antibody, has been suggested as a potential healing therapeutic following glaucoma surgery. Here, we aimed to improve the bioavailability of bevacizumab when used as an adjunct therapy to non-penetrating deep sclerectomy (DS) by using a bevacizumab-methylcellulose mixture (BMM). Ten previously non-operated eyes in ten patients diagnosed with primary open angle glaucoma underwent DS with a subconjunctival injection of 0.3 ml of BMM (bevacizumab 3.75 mg incorporated into 4% methylcellulose) at the surgical site. Bevacizumab release was evaluated in vitro using size-exclusion high performance liquid chromatography (HPLC). Intraocular pressure (IOP), bleb morphology, corneal endothelial cell count (CECC), and complications were evaluated at 6 months after surgery. Using HPLC, bevacizumab was detected in BMM for up to 72 h. Moreover, all surgical blebs remained expanded with hyaline material during the first week. A significant IOP reduction (mean ± SD= -10.3 ± 5.4 mmHg, P<0.001) and diffuse blebs were observed at the final follow-up period. Although CECC was slightly reduced (-7.4%), no complications were observed. In conclusion, bevacizumab was released from BMM, and the use of this innovative mixture yielded good results following DS with no complications. Further studies are required to determine its efficacy prior to establishing BMM as an adjunct treatment for penetrating and non-penetrating glaucoma surgeries.